2015
DOI: 10.1103/physrevlett.114.238002
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the Free-Fall Arch Paradox in Silo Discharge

Abstract: Several theoretical predictions of the mass flow rate of granular media discharged from a silo are based on the spontaneous development of a free-fall arch region, the existence of which is still controversial. In this Letter, we study experimentally and numerically the particle flow through an orifice placed at the bottom of 2D and 3D silos. The implementation of a coarse-grained technique allows a thorough description of all the kinetic and micromechanical properties of the particle flow in the outlet proxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
88
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(115 citation statements)
references
References 22 publications
19
88
1
Order By: Relevance
“…Moreover, they have found that, instead of considering a reduce outlet, a dilatancy at the outlet should be taken into account (φ 0 ≈ φ b [1−α 1 e −α 2 D ]). A recent work [10] has shown that close to the outlet, the particles are accelerated leading to the scaling of the velocity, but not in an idealised free fall. We adapted this model to propose a new expression for the flow rate :…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, they have found that, instead of considering a reduce outlet, a dilatancy at the outlet should be taken into account (φ 0 ≈ φ b [1−α 1 e −α 2 D ]). A recent work [10] has shown that close to the outlet, the particles are accelerated leading to the scaling of the velocity, but not in an idealised free fall. We adapted this model to propose a new expression for the flow rate :…”
Section: Resultsmentioning
confidence: 99%
“…D is reduced by kd avg due to boundary effects, where d avg characterizes the grain size, and k is an order-one constant [2]. Recent studies [17,18] have provided micromechanical insights into this equation with a coarse-grain technique. An important open question concerns the relevance of this relation for non-spherical particles.…”
mentioning
confidence: 99%
“…When the outlet diameter is smaller than about 5 particle diameters [9][10][11][12][13], clogs form after some time at the orifice and block further outflow, mostly unwanted. Spontaneous arch formation [14,15], the preceding kinetics [16], as well as the inherent force distributions [17,18] have been analyzed in the literature. In order to study the geometry and statics of such clogs, often 2D container geometries are chosen.…”
mentioning
confidence: 99%